(untitled) (Fiep Bulletin - online, 2014)
Much even so the violence if reveals indifferently of the age band, it is in the daily pay-adolescence and the adolescence that it can surpass the tolerable limits. The revolt, typical characteristic of these young that passes for a transformation of the body, that they suffer, each time more precociously, the influence of psicossociais factors in the production of hormones, it can for questions of learning of behaviors or partner-economic difficulties if transform into aggressiveness and violence. This article had for objective to show that the Physical Education can contribute, pedagogically, as a way of social integration young them in the school, it has seen that its practical provides the contact between the same ones, representing this the necessary condition for the game of the life, this contributing for learning in general e, in special, for the learning of proper moral rules to the conviviality in society.